An Optimal Fuzzy Logic-based PI Controller for the Speed Control of an Induction Motor using the V/F Method - Mugheri, N. H.; Keerio, M. U. (Engineering, Technology & Applied Science Research, 2021)
The Induction Motor (IM) is popular because of its low price, higher efficiency, and low maintenance cost. A comparative analysis of IM speed controllers using Voltage/Frequency (V/F) control or Scalar Control (SC) is presented in this paper. SC is commonly used due to its ease of implementation, simplicity, and low cost. To decrease the difficulty and cost of hardware implementation, this paper proposes an optimal Fuzzy Proportional Integral (Fuzzy-PI) controller. Firstly, the speed of IM using the V/F control technique is discussed. Then, speed control of IM using a conventional PI controller is performed. Finally, a simplified-rules Fuzzy-PI controller is developed in MATLAB/SIMULINK and its performance is compared with that of open-loop SC and the traditional PI controller. The performance of the simplified-rules Fuzzy-PI controller is superior to that of an open-loop constant V/F control and a conventional PI controller.